2020
DOI: 10.1371/journal.pone.0237884
|View full text |Cite
|
Sign up to set email alerts
|

The role of disulfide bonds in a Solanum tuberosum saposin-like protein investigated using molecular dynamics

Abstract: The Solanum tuberosum plant specific insert (StPSI) has a defensive role in potato plants, with the requirements of acidic pH and anionic lipids. The StPSI contains a set of three highly conserved disulfide bonds that bridge the protein's helical domains. Removal of these bonds leads to enhanced membrane interactions. This work examined the effects of their sequential removal, both individually and in combination, using all-atom molecular dynamics to elucidate the role of disulfide linkages in maintaining over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 55 publications
(87 reference statements)
0
4
0
Order By: Relevance
“…Thus, changes in the protein structure as a function of pH and denaturation could make these sites available to react with the isothiocyanate. Aldehyde-lysine and amine-carbonyl group formation are considered common causes of flavor alterations in high-protein products. , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, changes in the protein structure as a function of pH and denaturation could make these sites available to react with the isothiocyanate. Aldehyde-lysine and amine-carbonyl group formation are considered common causes of flavor alterations in high-protein products. , …”
Section: Resultsmentioning
confidence: 99%
“…Aldehyde-lysine and amine-carbonyl group formation are considered common causes of flavor alterations in high-protein products. 20,21 In summary, a C 14 methodology has been developed for the quantification of covalent bond formation between BLG and selected flavor compounds. Of the flavor compounds studied, PEITC showed the highest reactivity with up to ca.…”
Section: -Undecanone (Udo) Anantharamkrishnan Et Al (2020)mentioning
confidence: 99%
“…These interactions are usually irreversible. The binding of sulfur compounds to proteins can also be classified as covalent interactions ( 9 , 41 ). Anantharamkrishnan et al ( 11 ) showed that covalent bonds were formed between β-lactoglobulin and aldehydes, mercaptans and furans containing functional groups, resulting in Schiff base, Michael addition and disulfide bonds.…”
Section: Interaction Of Myofibrillar Protein With Flavor Substancementioning
confidence: 99%
“…Nevertheless, Cys plays a key role in enzyme function and protein structure stabilization (Paulsen & Carroll, 2013; Poole, 2015). Cys can form structural disulfide bonds that are fundamental for the proper folding of a wide range of proteins (Dupuis et al., 2020; Marshall et al., 2010; Trivedi et al., 2009). When located in the active site of an enzyme, Cys residues can fulfill a catalytic function by forming covalent bonds with the substrate, as observed for thioredoxins, glutaredoxins, peroxiredoxins, and glyceraldehyde‐3‐phosphate dehydrogenases (Zaffagnini, Fermani, et al., 2019).…”
Section: Introductionmentioning
confidence: 99%